KNOWLEDGE AND PRACTICE OF PHYSICAL ACTIVITY AMONG STUDENTS AT VIET NAM COLLEGE OF INDUSTRY AND TRADE, HO CHI MINH CITY IN 2024 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Background: Up to 81% of adolescents worldwide do not engage in sufficient physical activity. A recent study at Vietnam National University, Ho Chi Minh City (2022-2023) revealed that 68% of students meet the recommended levels of physical activity. These findings also recommend improving daily knowledge and practice of physical activity to enhance health and combat diseases.Objectives: To describe the status of knowledge and practice regarding physical activity among students at Viet Nam College of Industry and Trade in 2024 and some related factors.Subjects and Methods: A descriptive cross-sectional study was conducted on 424 students aged 18 and above, studying at Viet Nam College of Industry and Trade, Ho Chi Minh City in 2024. Data were collected through direct interviews using questionnaires and by observing physical activity practice with a monitoring checklist.Results: The proportion of students with correct knowledge about physical activity was 48.1%, while 70.8% had correct practice of physical activity. Factors related to knowledge of physical activity included sex (p
Keywords: Physical activity, knowledge, practice, students.